2017 UBT International Conference 2017
DOI: 10.33107/ubt-ic.2017.165
|View full text |Cite
|
Sign up to set email alerts
|

The changes in colour of biscuits during baking depending on time and different proportion of barley flour

Abstract: Biscuits hold an important position in food industry due to variety of taste, nutrition, crispiness and digestibility. The nutritional value of biscuits can be enhanced by fortification with a wide variety of protein rich cereal such as barley. Colour is essential to the manufacture of biscuits of good quality. During baking, complex chemical reactions take place in the biscuits, such as the Maillard reaction and caramelization. The aim of this study was to evaluate the changes in colour of biscuits during bak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The MP incorporated namkeens were slightly darker than the CN and this may be due to the reaction of polysaccharides. [ 43 ] ΔL values indicate the difference in lightness and darkness of the sample with respect to the CN. Negative ΔL values of −1.70, −0.42, −6.56, −4.28, −10.62, −8.55 of 1%, 5%, and 10% of GGN and PN indicated that the MP incorporated samples were darker when compared to the CN.…”
Section: Resultsmentioning
confidence: 99%
“…The MP incorporated namkeens were slightly darker than the CN and this may be due to the reaction of polysaccharides. [ 43 ] ΔL values indicate the difference in lightness and darkness of the sample with respect to the CN. Negative ΔL values of −1.70, −0.42, −6.56, −4.28, −10.62, −8.55 of 1%, 5%, and 10% of GGN and PN indicated that the MP incorporated samples were darker when compared to the CN.…”
Section: Resultsmentioning
confidence: 99%